Understanding heterogeneity in methane emissions from confinement-fed dairy and beef cattle supplemented with Bovaer®: a meta-analysis - Macdonald, Ainslie; Shephard, Richard; Hepworth, Graham; Eckard, Richard (Frontiers in Animal Science, 2025)
IntroductionEnteric methane (CH4) emissions from ruminant livestock production systems pose a significant challenge to efforts to mitigate global climate change. The novel feed additive 3-nitrooxypropanol (3-NOP) has the capacity to inhibit rumen methanogenesis and significantly reduce the volume of enteric CH4 emissions produced by livestock systems. However, heterogeneity in CH4 mitigation from 3-NOP supplementation prevents livestock producers from determining the actual impact of supplementation on CH4 emissions. This meta-analysis aimed to understand the variables responsible for the heterogeneity in CH4 mitigation from 3-NOP supplementation in confinement-fed beef and dairy cattle.MethodsUsing 30 in vivo studies (83 treatments) that continuously supplemented 3-NOP at a range of doses from 40mg to 338mg dose (mg 3-NOP/kg dry matter intake; DMI), a mixed-effects multistep regression examined the impact of 3-NOP supplementation on CH4 yield.ResultsOn average, 3-NOP supplementation reduced CH4 yield by 25.9% in beef cattle and 26.4% in dairy cattle, at the recommended dose of 60mg 3-NOP/kg DMI. Results showed that the anti-methanogenic potential of 3-NOP was influenced by 3-NOP dose (mg 3-NOP/kg DMI) and DMI kg/head-1/day-1.DiscussionAlthough studies showed a strong positive relationship between 3-NOP dose and CH4 emissions (P <0.0001), DMI was observed to have a greater influence of CH4 abatement than 3-NOP dose. This suggests that the volume and timing of CH4 production influences the availability of 3-NOP in the rumen during methanogenesis more than 3-NOP dose itself. This paper uses this understanding to develop equations that can estimate future CH4 abatement in real farm systems, allowing producers the capacity to quantify the impact of 3-NOP on their greenhouse gas emissions and receive recognition for avoided CH4 emissions. However, these equations are highly influenced by DMI and are only suitable for confinement-fed systems that consume an equal or greater volume of ration and are not a substitute for measuring CH4 emissions, which would provide producers with the actual volume of CH4 emissions avoided.